Preparation of MoS2 nanoflakes in a mixed solvent by liquid phase exfoliation (LPE) technique - Nusaiba Akter Saima; Khandker Saadat Hossain; Sabina Hussain (AIP Advances)
After the successful synthesis of graphene, the search area for 2D-nanomaterials became even larger. Currently, studies have been expanded from graphene to transition metal dichalcogenides such as molybdenum disulfide (MoS2), molybdenum diselenide (MoSe2), tungsten disulfide (WS2), and layered transition metal oxides. In this study, MoS2-nanoflakes were prepared by the liquid phase exfoliation technique. Binary mixtures of ethanol and deionized water in different percentages (100%, 80%, 60%, 40%, 20%, and 0%) were used as the solvent to synthesize the MoS2-nanoflakes in a large scale. The quality of the solvents for exfoliation was determined using the Hansen solubility parameters. The analysis revealed that 60% ethanol-to-water mixture worked better than all the other mixtures. This study explored the structural, morphological, and optical properties of the produced nanoflakes. The UV–Vis spectroscopy showed a rise in absorption intensity with increasing sonication time, indicating thickness reduction of the nanoflakes. In addition, the yield percentage increases up to 20% with increasing sonication time. From the atomic force microscope images, the average thickness of the MoS2-nanoflakes has been found to be ∼10 nm. However, it has been found that the thickness of the nanoflakes decreases with increasing sonication time. Fourier transform infrared spectroscopy has confirmed that there was no contamination. The lateral size of the nanoflakes has been determined using dynamic light scattering. For 60% ethanol solvent, the lateral size of the nanoflakes has been found to be 168.6 nm. The dispersion remained stable for ∼28 days.